Passive and active control of three dimensional buildings. - Arfiadi, Yoyong
The majority of the recent research effort on structural control considers two dimensional plane structures. However, not all buildings can be modelled as plane structures, thus limiting the capability of the proposed procedures only to regular and symmetrical structures. A new procedure is developed in this paper to analyse three dimensional buildings utilizing passive and active control devices. In the building model, the floors are assumed rigid in their own plane resulting in three degrees of freedom at each floor. Two types of active control devices utilizing an active tuned mass damper and an active bracing system are considered. The effect of passive mass dampers and active control force in the equations of motion is incorporated by using the Hamilton's principle. The passive parameters of the dampers as well as the controller gain is then optimized using a genetic based optimizer where the H2, H and L1 norms are taken as the objective functions.
Keywords: Three dimensional building; Structural control; H2 norm; H norm; L1 norm; Direct output feedback; Genetic algorithm